A Pragmatic analysis of fictional dialogues of male protagonists as a technique of characterization in selected stories from Jose Dalisay, Jr.'s Oldtimer and other stories - Ismael, Rachelle Christianne F.; Lazaro, Zenia P. (College of Arts and Letters, University of the Philippines Diliman, 2006)
In this study, the researchers examined the rhetorical exchanges of male protagonists in selected short stories form Dalisay's collection, Oldtimer and Other Stories. These dialogues were analysed using two key pragmatic principles: Grice's Cooperative Principle (CP) and Leech's Politeness Principle (PP). Leech merged these two principles into what he proposes to be called the Interpersonal Rhetoric framework (1983). The maxims that constitute the CP and the PP factors that are always present and at work in every interaction, since interlocutors are viewed as always cooperating conversationally and taking note of politeness in order for communicative exchanges to be successful. Even in the interlocutors' violations of the Interpersonal Rhetoric, they are still considered being "cooperative" because it is assumed that those violations still convey implicit meanings (or implicatures, according to Grice). the Interpersonal Rhetoric Framework is in turn bound by the interlocutors' individual contexts because it is withing these contexts that the maxims in the framework are employed. For each individual interlocutor, there is a varying individual context. These individual contexts are bound by the overall context of the situation which encompasses the whole interaction. By classifying the male p[protagonists' utterances according to the maxims under the Interpersonal Rhetoric they observe and/or violate, taking note of the frequencies of these observations and violations, and considering both the individual contexts of the characters and the context of the situation, the researchers made generalizations and conclusions about the characterization of the male protagonists. Based on the results of the pragmatic analysis in the study, the fictional dialogues of the male protagonists from the selected stories were found to highlight features in each protagonist's character. The following generalizations were made while taking into account not only the overall contexts which encompass the dialogues, but also the individual contexts in which each interlocutor is bound. The features of the male protagonists' character were found to have a pattern which reveals a strong sense of assertiveness, virility, and fortitude. This pattern is indicative of particular aspects of a Filipino male's traits and of Philippine culture in general. Examples of these are (1) the observance of the 'shame' culture especially for the adolescent male characters like Dado in "Revelations" and the narrator in"Cameo," (2) respect for authority especially for people who are in their old age as seen in the character of Dado in "Revelations", (3) strong family ties betwen Tulmek and Dug-ong in the "The Mirror", (4) patriarchy or male dominance as seen in the character of the Major in "Heartland", and as seen in the community of Tulmek, Dug-ong, and Sublay in "The Mirror, and (5) high regard for education as seen in the character of Teban, the old sweeper in "Revelations". Each story is a "slice" of Philippine life and experience. In general, through the pragmatic approach used in this study, a more systematic interpretation of the fictional dialogues of selected stories in Dalisay's collection is made possible. This is in comparison with a purely intuitive interpretation of the stories which would be based only on the researchers' own impressions. Hence, the maxims under the Interpersonal Rhetoric Framework can be said to be effective instruments in revealing the implicit out of the explicit. Moreover, the area of pragmatics once again proves to be useful in literary studies as it focuses on fictional dialogues as used to delineate the characterization of the male protagonists and provides new insights for literary interpretation.